Susceptibility to hepatocellular carcinoma is associated with genetic variation in the enzymatic detoxification of aflatoxin B1. - McGlynn, K A (1995)
Aflatoxin B1 (AFB1) has been postulated to be a hepatocarcinogen in humans, possibly by causing p53 mutations at codon 249. AFB1 is metabolized via the phase I and II detoxification pathways; hence, genetic variation at those loci may predict susceptibility to the effects of AFB1. To test this hypothesis, genetic variation in two AFB1 detoxification genes, epoxide hydrolase (EPHX) and glutathione S-transferase M1 (GSTM1), was contrasted with the presence of serum AFB1-albumin adducts, the presence of hepatocellular carcinoma (HCC), and with p53 codon 249 mutations. Mutant alleles at both loci were significantly overrepresented in individuals with serum AFB1-albumin adducts in a cross-sectional study. Mutant alleles of EPHX were significantly overrepresented in persons with HCC, also in a case-control study. The relationship of EPHX to HCC varied by hepatitis B surface antigen status and indicated that a synergistic effect may exist. p53 codon 249 mutations were observed only among HCC patients with one or both high-risk genotypes. These results indicate that individuals with mutant genotypes at EPHX and GSTM1 may be at greater risk of developing AFB1 adducts, p53 mutations, and HCC when exposed to AFB1. Hepatitis B carriers with the high-risk genotypes may be an even greater risk than carriers with low-risk genotypes. These findings support the existence of genetic susceptibility in humans to the environmental carcinogen AFB1 and indicate that there is a synergistic increase in risk of HCC with the combination of hepatitis B virus infection and susceptible genotype.